Awareness and constraints towards the implementation of green dentistry amongst dental students and private practitioners of West India - Shaiva Thakar; Niraj Kinariwala; Dhrusha Pandya; Nirav H Parekh; Niravkumar K Patel; Aastha Patel (Wolters Kluwer Medknow Publications, 2023)
Background: Dentistry is a resource-intensive discipline of healthcare that has a notable impact on the environment. Sustainability should be the major consideration for healthcare service providers to support climate change policies. Green dentistry is an efficient strategy for practicing eco-friendly dentistry. This study was conducted to assess the awareness, knowledge, and barriers to practicing green dentistry among dental practitioners and dental students. Materials and Methods: A cross-sectional, descriptive-analytical online questionnaire survey with 22 questions was carried out. Results: 51.8% of participants were not aware of the concept of green dentistry. Practitioners of the age group 20-30 years are more willing to transform their dental practice into green practice to reduce the carbon footprint of their clinic (P < 0.05). Chi-square data analysis shows that dental practitioners treating more than 20 patients in a week have a better awareness of the concept of green dentistry (P < 0.05). Conclusion: Within the limitations of this study, dental professionals in the younger age group are eager to transform their dental practices to green practices to lessen their clinics' carbon footprints. Financial constraints limit the implementation of green dentistry into clinical practice.